2020
DOI: 10.1039/d0qo00839g
|View full text |Cite
|
Sign up to set email alerts
|

Emissive tetraphenylethylene (TPE) derivatives in a dissolved state tightly fastened by a short oligo(ethylene glycol) chain

Abstract: The structural change in the excited state evidently plays a crucial role for quenching process of organic molecules exhibiting aggregation-induced emission (AIE, thus AIEgens) in the solution state. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…[22][23][24][25] Tetraphenylethene (TPE), a star AIE luminogen, is an ideal candidate for the experimental study of stereoisomerism by the asymmetrical substitutions of its CQC double bond. [26][27][28][29][30][31] The influence of TPE-based Z-/E-isomers on their assembled morphologies and luminescent properties has been widely reported experimentally, it is found that Z-/E-isomers with the same chemical formula display dramatically different morphologies and emission properties. 21,[32][33][34][35][36][37] For example, the crystalline state of Z-BETPE is a needle-shape with greenishblue emission, while that of E-BETPE is a bulk-like morphology with blue emission.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Tetraphenylethene (TPE), a star AIE luminogen, is an ideal candidate for the experimental study of stereoisomerism by the asymmetrical substitutions of its CQC double bond. [26][27][28][29][30][31] The influence of TPE-based Z-/E-isomers on their assembled morphologies and luminescent properties has been widely reported experimentally, it is found that Z-/E-isomers with the same chemical formula display dramatically different morphologies and emission properties. 21,[32][33][34][35][36][37] For example, the crystalline state of Z-BETPE is a needle-shape with greenishblue emission, while that of E-BETPE is a bulk-like morphology with blue emission.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum yield of TPE-Lac was measured using fluorescein as the standard. 63 The probe showed a decent fluorescence quantum yield ( φ F ) of 0.251. From this photophysical behaviour, we have fixed the excitation wavelength and water/THF percentage at 345 nm and 97%, respectively, for carrying out further studies.…”
Section: Resultsmentioning
confidence: 99%
“…Kokado synthesized emissive TPE derivatives 11 and 12 in a dissolved state by using tightly fixed short oligomeric (ethylene glycol) chains (Scheme 2c). 46 They formed a series of TPE macrocycles through intramolecular McMurry coupling, where the ortho -benzene ring was connected with the low polyethylene glycol chain. The substitution at the para and meta positions yielded cis isomers of TPE macrocycles, while in the case of short OEG chains, ortho -substitution resulted in trans isomers.…”
Section: Tpe-based Macrocycles With Dual-ring Topologymentioning
confidence: 99%